2015
DOI: 10.3389/fpls.2015.01098
|View full text |Cite
|
Sign up to set email alerts
|

Chitin Nanofiber Elucidates the Elicitor Activity of Polymeric Chitin in Plants

Abstract: Chitin, an N-acetyl-D-glucosamine polymer, is a component of fungal cell walls and a microbe/pathogen-associated molecular pattern that elicits plant defense responses. As polymeric chitin is difficult to handle due to its insolubility in water, many studies on chitin-induced immune responses have used water-soluble low-molecular weight chitin instead. Thus, it is unclear if polymeric chitin can induce resistance. Here, we examined the elicitor activity of chitin nanofiber (CNF) of submicron thickness prepared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 35 publications
1
53
0
Order By: Relevance
“…Such effects of shells or chitin-source treatments on growth promotion and/or host resistance have also been reported for other pathosystems such as cocoa/snail shells/Phytophthora megakarya [9], tobacco/nanochitin/Fusarium spp. [21], chilli/chitosan/Colletotrichum capsica [22], millet/chitosan derivatives/Pyricola grisea [23], tomato/crab shells/Fusarium oxysporum [24] and cocoa/oyster shells/P. megakarya [20] through the possible triggering of biochemical pathways associated with growth promotion and disease resistance [8] [25] [26].…”
Section: Discussionmentioning
confidence: 99%
“…Such effects of shells or chitin-source treatments on growth promotion and/or host resistance have also been reported for other pathosystems such as cocoa/snail shells/Phytophthora megakarya [9], tobacco/nanochitin/Fusarium spp. [21], chilli/chitosan/Colletotrichum capsica [22], millet/chitosan derivatives/Pyricola grisea [23], tomato/crab shells/Fusarium oxysporum [24] and cocoa/oyster shells/P. megakarya [20] through the possible triggering of biochemical pathways associated with growth promotion and disease resistance [8] [25] [26].…”
Section: Discussionmentioning
confidence: 99%
“…Worms such as superworms (Zophobas morio) and mealworms (Tenebro molitor) belongs to the darkling beetle (Tenebrionidae) family and are naturally voracious pests in agriculture, consuming dry grain stock even though they are food sources themselves in many societies 7 . Mealworms have been recently shown to be able to consume and metabolize plastics 8 safely, a capability attributed to commensal gut bacteria in these worms confirmed with 13 Ccarbon isotope tracing experiments 9 . At the worm stage, they can be kept at high density, and excrete nitrogen-rich waste in the form of frass 10 that can be potential fertilizers for plant crops.…”
Section: Introductionmentioning
confidence: 73%
“…The worms are also rich in chitin 11,12 , a chemical shown to improve the growth and the yields of plants [13][14][15] . More recently, superworms are also been reported to consume PS, and at a higher rate than mealworms 16 , showing promise in the use of superworms in the fight against plastics.…”
Section: Introductionmentioning
confidence: 99%
“…CH nanofibers (CNF) can be more feasibly used since they behave as a water-soluble material. Thus, they were tested for their elicitor capacity, and Egusa et al first showed that CNF enhanced resistance against pathogens in A. thaliana and rice [6]. More recently, when challenged with the fungal pathogens, cabbage and strawberry plants, grown in a mixture of soil and CNF, showed a reduction in the number of spots caused by Alternaria brassicicola and lesion size by Colletotrichum fructicola in respect to control plants [7].…”
Section: Chitin-based Polymersmentioning
confidence: 99%